1994
DOI: 10.1001/archinte.1994.00420140095012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Borreliacidal Antibodies by Flow Cytometry

Abstract: Detection of borreliacidal antibody, unlike indirect fluorescent antibody and enzyme immunoassay, is an accurate, highly specific serodiagnostic test for detection of Lyme disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…As seen in our experimental dogs, the levels of growth-inhibiting antibodies were low or the antibodies were missing after exposure to ticks. Eventually, a more sensitive test based on flow cytometry used by Callister et al (6) may provide a helpful tool for the diagnosis of early Lyme disease. At this time it is not clear whether this method will be applicable during the early stage of the disease, since it is not known when borreliacidal antibodies appear in detectable quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in our experimental dogs, the levels of growth-inhibiting antibodies were low or the antibodies were missing after exposure to ticks. Eventually, a more sensitive test based on flow cytometry used by Callister et al (6) may provide a helpful tool for the diagnosis of early Lyme disease. At this time it is not clear whether this method will be applicable during the early stage of the disease, since it is not known when borreliacidal antibodies appear in detectable quantities.…”
Section: Discussionmentioning
confidence: 99%
“…The color change in the culture medium induced by live spirochetes was found to be a reliable and less labor intensive method of measuring growth-inhibiting antibodies (26,36,37). Recently, it was shown that flow cytometry is a useful tool for identifying infected patients apparently with small quantities of borreliacidal antibodies (6).…”
mentioning
confidence: 99%
“…Detection of borreliacidal antibodies. Borreliacidal antibodies were detected with a flow cytometer as previously described (7,10,22). Briefly, a frozen aliquot of B. burgdorferi sensu stricto isolate 297 or 50772 was thawed, 200 l was inoculated into 6 ml of fresh BSK medium, and the cultures were incubated at 35°C for 72 h. Following incubation, the concentration of B. burgdorferi organisms was adjusted to 10 6 spirochetes per ml with fresh BSK medium.…”
Section: Methodsmentioning
confidence: 99%
“…More recently recombinant chimeric proteins have been created, combining critical epitopes from several immunodominant antigens [23]. Another experimental assay uses flow cytometry to detect borreliacidal antibodies which may be more clinically relevant [24]. However, a recent study found quite low sensitivity (11%) for this assay in active Lyme disease [14].…”
Section: Advancesmentioning
confidence: 99%